gọi 3 góc của tgiac MNP là: \(\widehat{M},\widehat{N},\widehat{P}\)
Ta có: \(\widehat{M}+\widehat{N}+\widehat{P}=3\widehat{M}+2\widehat{N}\)
\(\Leftrightarrow\widehat{P}=2\widehat{M}+\widehat{N}\)(1)
Lấy E thuộc MN sao cho MP=ME ta sẽ có:
\(\widehat{MPE}=\widehat{MEP}\)
Vậy: \(\widehat{P}=\widehat{MPE}+\widehat{NPE}=\widehat{MEP}+\widehat{NPE}=2\widehat{NPE}+\widehat{N}\)(2)
Từ (1) và (2) ta có: \(\widehat{M}=\widehat{NPE}\)
Ta dễ dàng có: \(\Delta MNP\sim\Delta PNE\left(g-g\right)\)
\(\Rightarrow NP^2=MN.NE\)
Vậy biểu thức=\(MN.NE+MN.MP-MN^2=MN\left(NE+ME-MN\right)=MN.0=0\)